2005
DOI: 10.1242/jcs.02405
|View full text |Cite
|
Sign up to set email alerts
|

The vacuolar proton-ATPase plays a major role in several membrane-bounded organelles inParamecium

Abstract: IntroductionThe vacuolar-proton-ATPase (V-ATPase) translocates protons across membranes against their electrochemical potential through ATP hydrolysis. The V-ATPase is responsible for the acidification of organelles like phagosomes, lysosomes, early endosomes, the trans-Golgi-network, dense core secretory granules and vacuoles of plants (Sun-Wada et al., 2003a;Nelson, 2003;Kluge et al., 2003). In some specialized cells of higher organisms, the enzyme is also localized in the plasma membrane and serves to secre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
89
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3

Relationship

5
3

Authors

Journals

citations
Cited by 48 publications
(90 citation statements)
references
References 56 publications
1
89
0
Order By: Relevance
“…Sequences encoding the Ins(1,4,5)P 3 -binding domain of IP 3 R N (S268-L658) were amplified by PCR using primers pBD-f (5Ј-gcgctgcagatgtcaacatcttggaaaattaatctt-3Ј) and pBD-rev (5Ј-cgcctcgagaacctaatcgttcaaatagatacaatta-3Ј), and cloned in a modified pPXV-GFP vector (Wassmer et al, 2005). Paramecium cells were transformed by microinjecting DNA into the macronucleus as described by Wassmer et al (Wassmer et al, 2005).…”
Section: Expression and Immuno-precipitation Of Gfp-fusion Proteinmentioning
confidence: 99%
See 1 more Smart Citation
“…Sequences encoding the Ins(1,4,5)P 3 -binding domain of IP 3 R N (S268-L658) were amplified by PCR using primers pBD-f (5Ј-gcgctgcagatgtcaacatcttggaaaattaatctt-3Ј) and pBD-rev (5Ј-cgcctcgagaacctaatcgttcaaatagatacaatta-3Ј), and cloned in a modified pPXV-GFP vector (Wassmer et al, 2005). Paramecium cells were transformed by microinjecting DNA into the macronucleus as described by Wassmer et al (Wassmer et al, 2005).…”
Section: Expression and Immuno-precipitation Of Gfp-fusion Proteinmentioning
confidence: 99%
“…The ORS generally consists of two identical units per cell, each composed of a contractile vacuole, with approximately six collecting canals to which a tubular membranous network is attached (reviewed in Allen and Naitoh, 2002). This network displays a part proximal to the collecting canals that has smooth membranes (smooth spongiome) and a distal part that is studded with V-type H (Allen et al, 1990;Allen, 1995;Fok et al, 1995;Tominaga et al, 1998;Wassmer et al, 2005) and which might be coupled not only to the wellestablished osmotically driven water influx (Grønlien et al, 2002) but possibly also to a hypothetical cation-exchange system (Stock et al, 2002a;Stock et al, 2002b). In the absence of a Ca 2+ -pump, Ca 2+ might, thus, be transported into the ORS.…”
Section: Introductionmentioning
confidence: 99%
“…Baf A1 blocks the V-ATPase activity causing neutralization of the acidic environment of endosomes. Baf A1 is routinely used as a suppressor of V-ATPases, and it is used to test whether specific viral entry is reliant on endosomal acidification (Clague et al, 1994;Drose & Altendorf, 1997;Jin et al, 2005;Wassmer et al, 2005). It has been widely used as a probe to study acid-mediated viral trafficking using a variety of virus models.…”
Section: Engulfmentmentioning
confidence: 99%
“…Chemical inhibitors are assumed to block the entry pathway at certain specific points and incomplete virus replication in the presence of inhibitor is presumed to indicate viral penetration using the pathway blocked by the drug. Commonly used drugs are chlorpromazine (prevents assembly and disassembly of clathrin lattices at the cell surface and on endosomes by inhibiting clathrin polymerization which blocks assembly of coated pits and is also a phospholipase A2 inhibitor, Blanchard et al, 2006); bafilamycin A1 (inhibits vacuolar proton ATPases inhibiting acidification of endosomes by blocking transport of protons into the vesicle, Clague et al, 1994;Drose & Altendorf, 1997;Wassmer et al, 2005); ammonium chloride (penetrates into the endosome increasing endosomal pH, Jin et al, 2002;Liebl et al, 2006); chloroquine (blocks assembly of clathrin coated pits and raises endosomal pH, Mani et al, 2006;Ros et al, 2002). Brefeldin A has no effect on the early endosome but inhibits vesicle transport and early-to-late endosome transition (Clague et al, 1994;Nebenfuhr et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast. by expressing the different endogenous isoforms of relevant subunits as fluorescent fusion proteins in Parantecium we could largely exclude their occurrence at trichocyst exocyto sis sites (Wassmer et al, 2005) where they should have shown up in the characteristic regular spacing. Therefore.…”
Section: A Membrane Fusion and Fissionmentioning
confidence: 99%